2021
DOI: 10.2174/2666796701999200918161400
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Insights into Structure-Function Relationship, Drug Targets and Drug Design Strategies for Novel-Coronavirus 2019

Abstract: Background: Novel coronavirus (2019-nCov) imposed deadly health calamity with unexpected disastrous situation alarming the globe for urgent treatment regimes. World Health Organization (WHO) termed the coronavirus disease as COVID-2019 on February 11, 2020 and announced its outbreak as pandemic on 11 March 2020. The first infection was noticed in Wuhan, Hubei province, China in December 2019 and it is believed that the corona-virus is transmitted to humans through bats as a reservoir and involving human to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The molecular docking approach is highly beneficial as the resultant lead compounds can be directly evaluated for clinical studies and drug development process. [8][9][10] This research work aimed at identifying novel quorum sensing inhibitors (QSIs) of target protein (LasR) of P. aeruginosa by using virtual screening studies. A supported literature by Borges A. et al, and Chourasiya et al, suggested that 'thiazoles derivatives' showed stronger interaction, better than that of native ligand (OHN) with the target protein (LasR).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular docking approach is highly beneficial as the resultant lead compounds can be directly evaluated for clinical studies and drug development process. [8][9][10] This research work aimed at identifying novel quorum sensing inhibitors (QSIs) of target protein (LasR) of P. aeruginosa by using virtual screening studies. A supported literature by Borges A. et al, and Chourasiya et al, suggested that 'thiazoles derivatives' showed stronger interaction, better than that of native ligand (OHN) with the target protein (LasR).…”
Section: Introductionmentioning
confidence: 99%